2007
DOI: 10.1016/j.vetmic.2006.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Absence of surface expression of feline infectious peritonitis virus (FIPV) antigens on infected cells isolated from cats with FIP

Abstract: Feline infectious peritonitis virus (FIPV) positive cells are present in pyogranulomas and exudates from cats with FIP. These cells belong mainly to the monocyte/macrophage lineage. How these cells survive in immune cats is not known. In this study, FIPV positive cells were isolated from pyogranulomas and exudates of 12 naturally FIPV-infected cats and the presence of two immunologic targets, viral antigens and MHC I, on their surface was determined. The majority of the infected cells were confirmed to be cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 15 publications
(15 reference statements)
0
19
0
1
Order By: Relevance
“…So at least in terms of CD16-expression, peripheral NK cells from FIP cats seem to be better equipped for ADCC. Although the relative increase was significant, the five-fold reduction in absolute NK cell numbers seen earlier, in addition to the absence of viral proteins in 50% of FIPV-infected cells and the rapid internalization of cell-surface bound antibodies in infected cells, somewhat lowers the impact of this finding (Cornelissen et al, 2007;Dewerchin et al, 2008).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…So at least in terms of CD16-expression, peripheral NK cells from FIP cats seem to be better equipped for ADCC. Although the relative increase was significant, the five-fold reduction in absolute NK cell numbers seen earlier, in addition to the absence of viral proteins in 50% of FIPV-infected cells and the rapid internalization of cell-surface bound antibodies in infected cells, somewhat lowers the impact of this finding (Cornelissen et al, 2007;Dewerchin et al, 2008).…”
Section: Discussionmentioning
confidence: 71%
“…The current hypothesis states that FIPV arises through mutation from the avirulent coronavirus feline enteric coronavirus (FECV) (Chang et al, 2010). Additionally, FIPV is very immune evasive, especially toward the humoral branch of immunity (Pedersen and Boyle, 1980;Cornelissen et al, 2007;Dewerchin et al, 2008). About 30 years ago, Pedersen and Black (1983) already stated that a strong cell-mediated immune response (CMI) is key to surviving a FIPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Even though only about 1 % of the monocytes was infected with FIPV, the fact that every infected monocyte was able to internalize its viral proteins adds to the likelihood that internalization occurs in vivo as well. In addition, we have found that FCoV-infected monocytes in naturally infected FIP cats show no membrane expression (Cornelissen et al, 2007). However, membrane expression returns after in vitro cultivation, which indicates that internalization might occur in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…In previous work, we reported that the membranebound viral proteins, the spike and the membrane protein, are internalized upon antibody binding, which results in the loss of detectable viral proteins on the plasma membrane (Dewerchin et al, 2006). The fact that no surface-expressed viral antigens can be found on FCoVinfected monocytes isolated from naturally infected FIP cats, and that surface expression returns after isolation and in vitro cultivation of the monocytes, is the first indication that this immune-evasion strategy also exists in vivo (Cornelissen et al, 2007). If internalization could be blocked, then the humoral immune system would be able to contribute to the elimination of infected monocytes either by antibody-dependent complement-mediated or antibody-dependent cell-mediated lysis.…”
Section: Introductionmentioning
confidence: 99%
“…Both processes result in the clearance of all detectable viral antigens from the plasma membrane of infected cells (Dewerchin et al, 2005;Dewerchin et al, 2006). FIPVinfected monocytes/macrophages isolated from naturally infected cats do not express viral proteins at their plasma membrane either (Cornelissen et al, 2007). Absence of viral proteins in the plasma membrane of infected monocytes can protect the infected cells from efficient ADCML.…”
mentioning
confidence: 99%